2021
DOI: 10.3233/jad-200941
|View full text |Cite
|
Sign up to set email alerts
|

Computational Evaluation of Interaction Between Curcumin Derivatives and Amyloid-β Monomers and Fibrils: Relevance to Alzheimer’s Disease

Abstract: Background: The most important hallmark in the neuropathology of Alzheimer’s disease (AD) is the formation of amyloid-β (Aβ) fibrils due to the misfolding/aggregation of the Aβ peptide. Preventing or reverting the aggregation process has been an active area of research. Naturally occurring products are a potential source of molecules that may be able to inhibit Aβ42 peptide aggregation. Recently, we and others reported the anti-aggregating properties of curcumin and some of its derivatives in vitro, presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Research points to many potentials. For example, the monomeric/oligomeric forms of Aβ can potentially be considered more toxic, due to their mobility and ability to be secreted and cross membranes in a less impeded manner; meanwhile, others show that the fibrillar forms are more toxic and need to be cleared [77][78][79][80][81][82]. Thus, are the exosomes gathering Aβ and clearing it or spreading it pathologically?…”
Section: Discussionmentioning
confidence: 99%
“…Research points to many potentials. For example, the monomeric/oligomeric forms of Aβ can potentially be considered more toxic, due to their mobility and ability to be secreted and cross membranes in a less impeded manner; meanwhile, others show that the fibrillar forms are more toxic and need to be cleared [77][78][79][80][81][82]. Thus, are the exosomes gathering Aβ and clearing it or spreading it pathologically?…”
Section: Discussionmentioning
confidence: 99%
“…This pleiotropic molecule is found in the rhizome of Curcuma longa , and is a diarylheptanoid with two O-methoxyphenols attached to a β-diketone moiety connected by two symmetrical olefinic bonds [ 13 ]. However, curcumin has low bioavailability due to its low solubility in water and instability at physiological pH, and transforms into ferulic acid, vanillin, dehydrozingerone, and curcumin glucuronide [ 1 , 14 , 15 , 16 , 17 ]. Curcumin displays anti-inflammatory effects by modulating several pathways involved in the inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…Protecting the reactive sites of curcumin (the aromatic rings and the keto-enol region) ( Figure 1 ) through the formation of derivatives could be an alternative strategy to improve its stability and take advantage of the benefits of this polyphenol [ 1 , 16 , 17 ]. Previous studies have shown that the phenolic rings and β-diketone moieties in the curcumin structure suffer from degradation by oxidation and hydrolysis [ 5 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we designed a small library of peptide inhibitors against Aβ monomer (PDB ID: 1IYT) and fibrillar structure (PDB ID: 2MXU). These peptides are designed based on homologous amyloidogenic region (16K-21A) by one/two-point mutation [19] and based on structural similarity with curcumin as reported by Orjuela et al [26]. These peptides are modified by terminal modifications (Nterminal Acetylation and C-terminal N-methylation), and by doing so, their inhibition efficiency increases gains stability against enzymatic degradation and improves hydrophobicity [27].…”
Section: Introductionmentioning
confidence: 99%